Second-Position Syncopation in European and American Vocal Music - Temperley, David (Empirical Musicology Review, 2019)
I define a second-position syncopation as one involving a long note or accent on the second quarter of a half-note or quarter-note unit. I present a corpus analysis of second-position syncopation in 19th-century European and American vocal music. I argue that the analysis of syncopation requires consideration of other musical features besides note-onset patterns, including pitch contour, duration, and text-setting. The corpus analysis reveals that second-position syncopation was common in English, Scottish, Euro-American, and African-American vocal music, but rare in French, German, and Italian vocal music. This suggests that the prevalence of such syncopations in ragtime and later popular music was at least partly due to British influence.